THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN MEDIATING THE RELATIONSHIP BETWEEN LEVERAGE AND TAX AGGRESSIVENESS - Janudin; Hestu Nugroho Warasto (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates the role of Corporate Social Responsibility (CSR) in mediating the relationship between leverage and tax aggressiveness in primary consumer goods companies, specifically the food and beverage subsector, listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a quantitative approach, this research analyzes 100 firm-year observations from 20 companies selected through purposive sampling. Data were examined using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that leverage does not have a significant direct effect on tax aggressiveness, nor does it significantly influence CSR disclosure. Furthermore, CSR is found to have a positive but insignificant effect on tax aggressiveness. Mediation analysis reveals that CSR does not mediate the relationship between leverage and tax aggressiveness. These findings suggest that corporate tax aggressiveness in the primary consumer goods sector is not primarily driven by leverage or CSR practices, but may be influenced by other organizational and institutional factors. This study contributes to the literature by providing empirical evidence on the limited mediating role of CSR in corporate tax behavior within an emerging market context.